Predictive value of soluble suppression of tumorigenicity 2 in atrial fibrillation: a systematic review and meta-analysis - Chen, Pengfei; Zhang, Jie; Du, Jianpeng; Shi, Dazhuo; Zhang, He (Frontiers in Cardiovascular Medicine, 2024)
Purpose Atrial fibrosis is the main pathological basis for the pathogenesis and progression of atrial fibrillation (AF). Soluble suppression of tumorigenicity 2 (sST2) is involved in fibrosis. Recent studies have explored its predictive value in AF outcomes. We performed this study to assess whether sST2 is an independent biomarker of AF outcomes and explore the potential mechanism. Methods PubMed, Web of Science, EMBASE, and Cochrane Library databases were searched systematically from inception through July 1, 2023, to identify relevant studies. Outcomes of interest included occurrence, recurrence, and major adverse cardiac events (MACEs) of AF. This meta-analysis was reported following the criteria outlined in PRISMA 2020, and the protocol was registered in PROSPERO (number: CRD42023459789). All statistical analyses were performed using the STATA version 16. Result Twenty four studies with 14,755 patients were included in the meta-analysis. The meta-analyses found that sST2 was significantly associated with the risk of occurrence [HR:1.04, 95% CI: 1.02–1.07, P < 0.01; I2 = 67.8%], recurrence [HR:1.09, 95% CI: 1.02–1.16, P < 0.01; I2 = 89.5%], and MACEs (HR:1.60, 95% CI: 1.13–2.27, P < 0.01; I2 = 82.0%) of AF. Furthermore, patients with AF showed higher sST2 than controls without AF (SMD: 0.41, 95% CI: 0.27–0.54, P < 0.01; I2 = 0%), and AF patients with recurrence after catheter ablation (CA) showed significantly higher sST2 than those without recurrence (SMD: 0.81, 95% CI: 0.33–1.28, P < 0.01; I2 = 83.9%). Sensitivity analyses showed that the outcomes were stable. Conclusions Higher sST2 was association with an increased risk of occurrence, recurrence, and MACEs of AF. Assessing sST2 can be used as a potential screening method to predict AF outcomes. Systematic Review Registration PROSPERO (CRD42023459789).